2022
DOI: 10.3390/children9101425
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Serum Levels Can Enhance the Diagnostic Power of Standard Blood Tests for Acute Appendicitis

Abstract: Background: The diagnosis of acute appendicitis (AA) remains challenging, especially in pediatrics, because early symptoms are not specific, and the younger the patient the more difficult their interpretation is. There is a large degree of agreement between pediatric surgeons on the importance of an early diagnosis to avoid complicated acute appendicitis (CAA) and its consequences. The aim of this study is to assess if Interleukin 6 (IL-6) could enhance the sensitivity (Sn) and specificity (Sp) of the currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The association between higher concentrations of IL-6 and complicated appendicitis is in line with the results from previous studies 28 30 . IL-6 is a pro-inflammatory cytokine produced by a variety of cells including macrophages, T cells, endothelial cells and fibroblasts, and stimulates the synthesis of acute phase reactants such as CRP, fibrinogen and serum amyloid A 31 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The association between higher concentrations of IL-6 and complicated appendicitis is in line with the results from previous studies 28 30 . IL-6 is a pro-inflammatory cytokine produced by a variety of cells including macrophages, T cells, endothelial cells and fibroblasts, and stimulates the synthesis of acute phase reactants such as CRP, fibrinogen and serum amyloid A 31 .…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, this study adds evidence supporting the previously indicated association between IL-6 and complicated appendicitis. However, the AUC for IL-6 was found to be 0.75, indicating only a moderate discriminatory ability in predicting complicated pediatric appendicitis, which is in line with previous studies that have found the AUC for IL-6 to be 0.70–0.77 28 30 . Studying the diagnostic property of IL-6 along with other diagnostic aids, such as clinical prediction scores, could offer valuable insights.…”
Section: Discussionsupporting
confidence: 88%
“…Appendicitis, a common surgical emergency affecting millions of people worldwide, has historically been viewed as an isolated condition, with its resolution by appendectomy typically considered a definitive cure [ 5 , 6 ]. Recently, several biochemical markers including IL-6 (which is synthesized in the liver) and bilirubin have been established to predict a complicated clinical course, e.g., due to organ perforation [ 7 , 8 , 9 ]. A growing body of research has shed new light on the long-term consequences of appendicitis beyond the acute phase.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to physical examination and image diagnosis, numerous laboratory markers such as white blood cells, neutrophil granulocytes, C-reactive protein, interleukins, sodium, bilirubin, red blood cell distribution width, mean platelet volume, etc. [4][5][6][7][8], as well as various scoring scales, help us to diagnose acute appendicitis [9][10][11]. Although acute appendicitis is the most common surgical abdominal pathology in children, it is still a challenge and diagnostic dilemma for pediatric surgeons despite all available diagnostic modalities.…”
Section: Introductionmentioning
confidence: 99%